The impact of the water-to-cement ratio on the surface morphology of cementitious materials. (November 2020) - Chuta, Edgar; Colin, Johan; Jeong, Jena
Abstract: In the present work, we have studied the impact of the variation of the water-to-cement (W/C) ratio on the roughness and lightness in cementitious materials surfaces. For this purpose, we have manufactured cement pastes and mortars in 4*4*16 c m 3 metal molds. We have used a spectrocolorimeter to determine the lightness of the surfaces and a digital microscope to measure their roughness. The terms lightness L * were used to characterize the color and the coefficients of the surface development R S to characterize the roughness. From our results, we have observed the increase of surface lightness when the W/C ratio increases, as well as the decrease of the roughness with the increase of the W/C ratio. Thus, there is an inverse relationship between lightness and roughness. On the other hand, the presence of sand in the mortars generates rougher and darker surfaces than in cement pastes. This phenomenon could be due to the absorption coefficient of the sands that absorb the water and therefore reduce the amount of water present in the pastes, thus generating darker surfaces. Highlights: Effect of the variation of the quantity of formulation water on the lightness of the hardened cementitious materials. Effect of surface roughness on lightness L * of the hardened cementitious materials. Variation of the porosity as a function of the increase of the water-to-cement ratio. Effect of sand on the appearance of the cement paste.